2013
DOI: 10.1590/abd1806-4841.20132192
|View full text |Cite
|
Sign up to set email alerts
|

Tattoos on 18-year-old male adolescents - Characteristics and associated factors

Abstract: BACKGROUND Prevalence of tattoos is around 10-26% in men and 10-22% in women, and can involve negative effects such as: regret, removal attempts, physical and biological changes of the skin and association with some viral diseases. OBJECTIVE to determine the prevalence, characteristics and factors associated with tattoos in recruiters joining the military. METHODS the recruiters were examined by dermatologists that documented the presence or absence of tattoos, as well as their sizes, colors, designs and patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…Our findings suggest the necessity of researching the epidemiology of tattoos in Latin American countries. We failed to find large studies about tattooing in general populations in South America [4]. However, Latin American football teams enrolled in the FIFA World Cup 2018 had the highest prevalence of tattooed players [5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest the necessity of researching the epidemiology of tattoos in Latin American countries. We failed to find large studies about tattooing in general populations in South America [4]. However, Latin American football teams enrolled in the FIFA World Cup 2018 had the highest prevalence of tattooed players [5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in rates may reflect variations in sanctioning within separate settings, with peer group pressure playing a significant role. In Brazil for example, tattooing was not introduced until 1959 and the practice is illegal for minors in some states[ 6 ]. A survey conducted among a sample of 18-year-old Brazilian military recruits ( n = 1968) revealed that about 11% of recruits had tattoos, of which 66% had a single tattoo and 21% had two tattoos, with the remainder having > 2 tattoos[ 6 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…In Brazil for example, tattooing was not introduced until 1959 and the practice is illegal for minors in some states[ 6 ]. A survey conducted among a sample of 18-year-old Brazilian military recruits ( n = 1968) revealed that about 11% of recruits had tattoos, of which 66% had a single tattoo and 21% had two tattoos, with the remainder having > 2 tattoos[ 6 ]. A large majority of tattooed recruits (80%) had obtained their first tattoo before the age of 18.…”
Section: Epidemiologymentioning
confidence: 99%
“…In comparison with the international literature, there is a dearth of empirical psychological research in the Brazilian context (or with the Brazilian population).Most Brazilian studies are theoretical and employ a qualitative approach (Bicca, Duquia, Breunig, Souza, & Almeida, 2013;Corso & Corso, 2014;Dadalte, Mariano, Pedrão, & Soares, 2013;Macedo & Paravidini, 2014;Macedo, Paravidini, & Próchno, 2014;Pinheiro & Carvalho, 2017;Rodriguez & Carreteiro, 2014), viewing tattoos mostly as a form of subjectivation, as a search for identity through symbolic means. Studies with quantitative and psychometric approaches are thus lacking in the Brazilian context (Conti et al, 2012;Gouveia, et al, 2010;Medeiros, Gouveia, Pimentel, Soares, & Lima, 2010).…”
Section: Introductionmentioning
confidence: 99%